Olah Produk Tanaman Pisang Dalam Peningkatan Ekonomi Masyarakat Desa Karanglo Kidul Kecamatan Jambon Kabupaten Ponorogo - Asyari, M. Hasyim; Almadani, M. Asip (Journal of Community Development and Disaster Management, 2023)
Based on the results of the team's survey in Dukuh Tengah, there are potential assets that can be developed, including banana plants. Plants that do not have this season grow a lot in the environment of Dukuh Tengah, therefore in this discussion took the theme with the title "Training on processing food products to increase the Selling Value of banana plants in Dukuh Tengah village of Karanglo Kidul". The process of processing bananas into steamed sponges is very simple, simply by using existing tools and ingredients that are easy to obtain. So we use the demonstration method to carry out training on processing banana steamed sponges in the middle village of Karanglo Kidul Village, so that the people of the middle village can easily understand and practice directly processing bananas into steamed sponges in their homes. By making banana plant assets that are processed into banana steamed sponges that have more selling price value and of course this activity can improve the quality of human resources of the dukuh tengah community who are innovative and creative. Hopefully the team hopes that later, the results of the banana steamed sponge processing training can increase economic results and can increase public insight and knowledge about banana processing innovations so that they have more selling value.